Gender equality approaches in water, sanitation, and hygiene programs: Towards gender-transformative practice - MacArthur, Jess; Carrard, Naomi; Mott, Jose; Raetz, Stuart; Siscawati, Mia; Willetts, Juliet (Frontiers in Water, 2023)
The recent (re-)emergence of gender-transformative approaches in the development sector has focused on transforming the gender norms, dynamics, and structures which perpetuate inequalities. Yet, the application of gender-transformative approaches within water, sanitation, and hygiene (WASH) programing remains nascent as compared with other sectors. Adopting a feminist sensemaking approach drawing on literature and practice, this inquiry sought to document and critically reflect on the conceptualization and innovation of gender-transformative thinking in the Australian Government’s Water for Women Fund. Through three sensemaking workshops and associated analysis, participants developed a conceptual framework and set of illustrative case examples to support WASH practitioners to integrate strengthened gender-transformative practice. The multi-layered framework contains varied entry points to support multi-disciplinary WASH teams integrating gender equality, as skills and resources permit. Initiatives can be categorized as insensitive, sensitive, or responsive, and prompted by five common motivators (welfare, efficiency, equity, empowerment, and transformative equality). The framework has at its foundation two diverging tendencies: towards instrumental gender potential and towards transformative gender potential. The article draws on historical and recent WASH literature to illustrate the conceptual framework for three key areas: (i) community mobilization, (ii) WASH governance, service provision and oversight and (iii) WASH-related enterprise development. The illustrative examples provide practical guidance for WASH practitioners integrating gendered thinking into programs, projects, and policies. We offer a working definition for gender-transformative WASH and reflect on how the acknowledgement, consideration, and transformation of gender inequalities can lead to simultaneously strengthened WASH outcomes and improved gender equality.